Assessing the effects of information and communication technologies on organizational development: business values perspectives. Issue 1 (2nd January 2020) - Saleem, Farrukh; Salim, Naomie; Altalhi, Abdulrahman H.; Ullah, Zahid; AL-Malaise AL-Ghamdi, Abdullah; Mahmood Khan, Zahid
ABSTRACT: Information and communication technology (ICT) projects for organizational development deal with market challenges, information handling, and the integration of multiple information systems (IS) in an organization. This research investigates how ICT projects (IS systems, etc.) affect the strategic, social, and human development in an organization. Previous studies have highlighted the advantages of ICT portfolio management techniques and return on investment approaches; the current research focused primarily on measuring business value on investment perspective. Therefore, based on the findings from the literature review, an integrated framework was proposed and validated using the case study in Saudi Arabia to evaluate the effects of ICT/IS projects from a managerial perspective. The framework consisted of a list of processes, criteria, and sub-criteria for different kinds of extracted features to measure the impact of ICT/IS projects. Our findings demonstrated that the effects of ICT projects are not limited to social and economic development, but are also categorized as strategic, managerial, informational, operational, transactional, organizational, infrastructure, and transformational development. It is hoped that the findings of the current study can inform ICT decision makers, experts, and researchers who have investigated and are doing research in this area.